Estimated Dietary Polyphenol Intake and Its Seasonal Variations among Japanese University Students - FUKUSHIMA, Yoichi; KONDO, Kazuo; TAGUCHI, Chie; IWASHIMA, Tomomi; TANAKA, Miori; KISHIMOTO, Yoshimi; TAKEUCHI, Ikue (Journal of Nutritional Science and Vitaminology, 2019)
The intake of polyphenols among Japanese has been estimated in several adult populations, but there has been no information regarding their intake among young adults, especially in those in their twenties. We conducted a food frequency questionnaire (FFQ)-based dietary assessment four times a year (once in each season) among Japanese university students and evaluated the total polyphenol intake across and within seasons. Forty-nine subjects (aged 20.7±0.6 y) completed our FFQ regarding polyphenol intake in February, May, August, and November 2016. We then calculated their total polyphenol intake using our polyphenol content database. The mean intake of total polyphenol across the seasons was 567±236 mg/d, which was largely sourced from beverages (62%). No significant differences were found in the total polyphenol intake or polyphenol intake from beverages among the four seasons. By contrast, we observed significant seasonal differences in the subjects’ polyphenol intake from food; the polyphenol intake from food in February (255 mg/d) was significantly higher than that in May (215 mg/d), August (187 mg/d) and November (196 mg/d) (p<0.0001). These findings should assist in future estimations of dietary polyphenol intakes that consider differences according to age and season.